Effect of the pandemic on prehospital management of patients with mental and behavioral disorders: a retrospective cohort study - Kintrilis, Nikolaos; Blek, Natasza; Blek, Sergiusz; Olkiewicz, Aleksandra; Ladny, Jerzy Robert; Szarpak, Lukasz (Frontiers in Public Health, 2023)
The novel severe acute respiratory syndrome coronavirus (SARS-CoV-2) infection and the accompanying coronavirus disease (Covid-19) have shifted the priority of human and technical resources toward their handling, thus affecting the usual standards of care for populations diagnosed with other clinical entities. The phenomenon becomes even more apparent in patients with presenting symptoms of mental and behavioral disorders, a category already vulnerable and underrepresented in regard to its prehospital approach and management. For the purposes of the current retrospective cohort study, we used records of the Polish National Emergency Medical Service Command Support System for the time period between April 1, 2019 and April 30, 2021, the official register of medical interventions delivered in Poland by Emergency Medical Services (EMS). We aimed to examine the potential impact of the COVID-19 pandemic across the Masovian Voivodeship on individuals seeking medical care for mental and behavioral disorders pertaining in the “F” category of the International Statistical Classification of Diseases and Related Health Problems, 10th Revision (ICD-10). We examined the individuals’ baseline characteristics, prehospital vital parameters and EMS processing times in a population of 59,651 adult patients (04/2019–03/2020, 28,089 patients, 04/2020–03/2021, 31,562 patients) handled by EMS teams. Compared to pre-COVID-19, EMS personnel handled fewer patients, but more patients required mental and behavioral care. Throughout the duration of the pandemic, all prehospital time periods were significantly delayed due to the increased time needed to prepare crew, vehicles, and technical equipment to ensure COVID-19 prevention and overcrowding in Emergency Departments (EDs).